Haploinsufficiency of ARID1B, a member of the SWI/SNF-a chromatin-remodeling complex, is a frequent cause of intellectual disability - Hoyer, Juliane; Rappold, Gudrun (The American journal of human genetics, 2012)
Intellectual disability (ID) is a clinically and genetically heterogeneous common condition that remains etiologically unresolved in the majority of cases. Although several hundred diseased genes have been identified in X-linked, autosomal-recessive, or syndromic types of ID, the establishment of an etiological basis remains a difficult task in unspecific, sporadic cases. Just recently, de novo mutations in SYNGAP1, STXBP1, MEF2C, and GRIN2B were reported as relatively common causes of ID in such individuals. On the basis of a patient with severe ID and a 2.5 Mb microdeletion including ARID1B in chromosomal region 6q25, we performed mutational analysis in 887 unselected patients with unexplained ID. In this cohort, we found eight (0.9%) additional de novo nonsense or frameshift mutations predicted to cause haploinsufficiency. Our findings indicate that haploinsufficiency of ARID1B, a member of the SWI/SNF-A chromatin-remodeling complex, is a common cause of ID, and they add to the growing evidence that chromatin-remodeling defects are an important contributor to neurodevelopmental disorders.